University Social Responsibility:Concept Of Transformative Breakthrough Based On Sustainable Development - Cahya, Bayu Tri; Baihaqi, Jadzil; Rohmah, Farida (Proceedings of Annual Conference for Muslim Scholars, 2019)
This article discusses about social responsibility from the point of view of higher education. The university in general is an institution with the highest honor in the academic environment. Then the university becomes the instrument of social climbing for most people in the society of developing countries. University social responsibility (USR) is a principle for social movements, which uses an ethical approach to develop and engage with local and global communities to maintain ecological, environmental, technical, social, and economic development. USR acts is a crucial player for social change because USR implies having an ethical quality policy, which regulates the performance of the university community. USR has an impact not only on universities but also on the global community and society. Keywords: University, Social Responsibility, Community Development